Cardiovascular risk in patients with psoriasis, psoriatic arthritis, and rheumatoid arthritis: a prospective study of data from the Secure Anonymised Information Linkage databank. (November 2016) - Cooksey, Roxanne; Brophy, Sinead; Kennedy, Jonathan; Guiterrez, Fabiola Fernandez; Pickles, Tim; Davies, Ruth; Piguet, Vincent; Choy, Ernest
Abstract: Background: The increased risk of cardiovascular disease in individuals with rheumatoid arthritis, psoriatic arthritis, and psoriasis is well known. However, the precise cardiovascular risk in psoriasis and psoriatic arthritis is less understood, particularly the relative contribution of traditional cardiovascular risk factors, such as obesity, smoking, and systemic inflammation as measured by C-reactive protein and erythrocyte sedimentation rate. The objective of this study was to compare the incidence of major adverse cardiac events (MACE) among patients with rheumatoid arthritis, psoriatic arthritis, and psoriasis with population controls adjusting for traditional cardiovascular risk factors, systemic inflammation, and disease-modifying anti-rheumatic drug (DMARD) treatment to better define cardiovascular risk in patients with these conditions. Methods: The study used linked, routinely collected Welsh health data from 1999 to 2013 available from the Secure Anonymised Information Linkage (SAIL) databank, which includes datasets from general practice (GP), hospitals, and rheumatology clinics. Incidence and first occurrence of a MACE was investigated in individuals who were present in the GP system and positive for Read codes for rheumatoid arthritis (n=8650), psoriatic arthritis (2128), psoriasis (24 630), and controls without codes for the conditions investigated (1 187 706). We controlled for traditional cardiovascular risk factors, such as age, sex, smoking, body-mass index, comorbidities (hyperlipidaemia, diabetes, and hypertension), and medication (non-steroidal anti-inflammatory drugs, DMARDs, and steroids). We used a Cox proportional hazard model with the st command in Stata (version 13). Findings: When controlling for traditional risk factors, cardiovascular risk was significantly increased for individuals with rheumatoid arthritis (number of MACE events 548, hazard ratio 1·2, 95% CI 1·0–1·3; p=0·038) and psoriasis (879, 1·1, 1·0–1·3; p=0·025), but not for those with psoriatic arthritis (43, 1·0, 0·7–1·5; p=0·887). No interaction between DMARDs and MACE occurrence was observed. Interpretation: There is an increased incidence of cardiovascular disease for patients with rheumatoid arthritis and psoriasis, but not for those with psoriatic arthritis. This finding demonstrates the varying mediators of cardiovascular risk across these conditions and highlights the importance of cardiovascular risk reduction strategies, especially for patients with rheumatoid arthritis and psoriasis, who may benefit from closer monitoring to help reduce the incidence of MACE. Funding: Supported by a Pfizer Inflammation Competitive Research Programme grant. The funder had no involvement in the study.